Značilnosti turističnega obiska slovenskih občin glede na državni izvor turistov - Cigale, Dejan (Geografski vestnik, 2010)
The paper analyzes data on tourist arrivals in Slovenian municipalities. It focuses on the question to what extent the structure of tourist arrivals is more or less heterogeneous in regard to the nationality of tourists visiting these municipalities and which factors influence it. For this purpose data of the Statistical Office of the Republic of Slovenia for the year 2008 were used. Analysis of the data showed that the following factors are among the ones that influence the arrival of tourists from large number of countries: above-average awareness of the destination, proximity of the most important traffic routes (highways) and tourism supply (tourist attractions), which is of interest for different tourist segments and which attracts also tourists from far-away countries.
Keywords: Slovenia; Slovenija; turisti; tuji turisti